Technology prevention of addictive behavior in children as part of a healthy lifestyle - Zolotova, A.D. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to develop a technology of social and educational prevention of addictive behavior in children as part of the organization of a healthy lifestyle. Material : a theoretical analysis and compilation of more than 50 sources of scientific and methodological literature. Applied methods of modeling and design of social and educational activities. Results : the technology of social and educational prevention of addictive behavior of children in the territorial community. The main components of addictive behavior prevention technologies children are: diagnostic levels of addictive behavior of children in the territorial community; goal-prevention technologies, the choice of technology development or prevention of addictive behavior in children, preparation and planning of prevention, the introduction of technology, expertise and evaluation of the effectiveness of the technology deployed, summing outcomes. Conclusions . prevention of addictive behavior is an integral part of the organization of a healthy lifestyle for children. Procedural embodiment prevention of addictive behavior of children in the life of the territorial community is represented as a developed social and educational technology.